2015
DOI: 10.1177/1362361315577517
|View full text |Cite
|
Sign up to set email alerts
|

The health status of adults on the autism spectrum

Abstract: Compared to the general pediatric population, children with autism have higher rates of co-occurring medical and psychiatric illnesses, yet very little is known about the general health status of adults with autism. The objective of this study was to describe the frequency of psychiatric and medical conditions among a large, diverse, insured population of adults with autism in the US. Participants were adult members of Kaiser Permanente Northern California enrolled from 2008-2012. ASD cases (N=1,507) were adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

69
841
16
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 856 publications
(938 citation statements)
references
References 54 publications
69
841
16
12
Order By: Relevance
“…15 A similar review of electronic health records by Croen and colleagues found that young adults with ASD experience increased rates of seizures, hypertension, dyslipidemia, sleep disorders, and nearly all psychiatric disorders compared to controls. 34 We similarly found higher rates of seizure disorder across all age groups and found high rates of depression, hypertension and allergies in young adults with ASD, although these approached the prevalence of the general population in our older age groups.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…15 A similar review of electronic health records by Croen and colleagues found that young adults with ASD experience increased rates of seizures, hypertension, dyslipidemia, sleep disorders, and nearly all psychiatric disorders compared to controls. 34 We similarly found higher rates of seizure disorder across all age groups and found high rates of depression, hypertension and allergies in young adults with ASD, although these approached the prevalence of the general population in our older age groups.…”
Section: Discussionsupporting
confidence: 58%
“…14,15,33,34 Most notably, we found a considerably higher prevalence of seizure disorders in adults with ASD in all age groups compared to the general population. We also found higher rates of depression, hypertension, and allergies in young adults with ASD, which approached the prevalence of the general population in our older age groups.…”
Section: Discussionmentioning
confidence: 56%
“…Although most autistic adults may not be seeking healthcare to address or Btreat^autism, they still require care for non-autism-related health issues and co-occurring conditions, such as seizures, anxiety, sleep disturbances, and gastrointestinal disorders. [6][7][8] Autistic adults face many barriers to receiving healthcare. A majority of…”
Section: Introductionmentioning
confidence: 99%
“…3 Authors of recent studies have indicated that adults with ASD also have elevated rates of psychiatric and major medical conditions. 4 Although the use and cost of health care services have been shown to be significantly elevated in adolescents with ASD, 5 robust estimates of the prevalence of medical and psychiatric conditions among adolescents and young adults with ASD are lacking.…”
mentioning
confidence: 99%